Rumours in the Protectorate of Bohemia and Moravia: 100 Days from the Life of an Occupied Country - Majewski, Piotr M. (Acta Poloniae Historica, 2022)
The article discusses rumours recorded by the German Security Service [Sicherheitsdienst, SD] in the Protectorate of Bohemia and Moravia between 1 January and 10 April 1943. The author pursues quantitative and qualitative analysis and discusses rumours shared by Czech and German inhabitants of the country. The analysis results indicate that early 1943 saw a real crisis of confidence in the state and the Nazi regime among Germans living in the Protectorate. The Czech public opinion had likely reached a turning point, still highly afraid of German repressions, but also with a growing hope for the defeat of the Reich and a swift end to the war.